(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
The article discusses in detail the role of agrotechnological measures in increasing soil fertility. Scientific data are presented on the use of mineral and organic fertilizers, the importance of microelements, as well as measures to improve the physicochemical properties of soils. Based on the analysis of scientific sources, it is emphasized that agrochemical practices are crucial for restoring soil fertility and increasing crop yields.